The Dynamics of Spiritual Well-Being for Prospective Mentors in the Haramain Student Mobility Program - Zahrany Tsabitah Noor Wibawa; Abdul Rozaq (UIN Sunan Gunung Djati Bandung, 2026)
This study explores the dynamics of spiritual well-being of prospective Hajj and Umrah guides participating in the Haramain Student Mobility Program. The role of a muthawwif demands strong spiritual preparedness, given the complexity of tasks such as assisting elderly pilgrims (47,384 people this year), regulatory changes, and the risk of fatigue and burnout. Previous research confirms that spirituality plays a crucial role in preventing fatigue and strengthening emotional resilience. The subjects were two Hajj and Umrah Management students from Walisongo State Islamic University (UIN) Semarang who participated in the Haramain Community Service Program (KKN) and aspired to become professional Hajj and Umrah guides. This study uses a descriptive qualitative approach, collecting data through in-depth interviews and analyzing them based on conceptual adaptations of the dimensions and indicators of the Spiritual Health And Life-Orientation Measure (SHALOM) developed by John W. Fisher. Consist of four domains of spiritual well-being: personal (self), communal, environmental, and transcendental (God). The results indicate a positive dynamic of spiritual well-being during the intense experience of the Haramain program. The personal domain reflects good self-knowledge, awareness of strengths and weaknesses, and positive thinking patterns. The communal domain demonstrated harmonious relationships, compassion, and a sense of family, despite minor friction. The environmental domain emphasized harmony with nature, concern for cleanliness, and awe of God's creation. Meanwhile, the transcendental domain was the strongest, strengthening personal relationships with God. Participants' spiritual well-being is achieved through the program experience, which simultaneously strengthens them to face challenges and prevents burnout. Participants' spiritual well-being was achieved through the program experience, strengthening them to face challenges and prevent burnout. It also served as a crucial foundation for developing the competencies of future Hajj and Umrah guides. These findings underscore the vital role of spiritual development in the professional education of mutawwif (traditional guides).